2022
DOI: 10.21608/aujst.2023.183546.1012
|View full text |Cite
|
Sign up to set email alerts
|

Image Segmentation Using Hybrid Optimization Algorithms: Review

Abstract: Image segmentation, often based on the properties of image pixels, is a widely used method in digital image processing and analysis to divide an image into multiple parts or areas. The main goal of image segmentation is to simplify the image for easier analysis. It would be very difficult to implement computer vision without performing image segmentation. An important component of computer vision is image segmentation, which has numerous commercial applications. Google and others Image-based search engines use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
0
0
Order By: Relevance
“…A histogram analysis may provide insight into an image's pixel value distribution. Original images typically exhibit distinct patterns and biases in their histograms, reflecting features like dominant colors, shapes, and textures [33][34][35][36]. Secure encryption techniques aim to disrupt these patterns and create a more uniform distribution of pixel values in the encrypted image's histogram.…”
Section: Analytical Histogrammentioning
confidence: 99%
“…A histogram analysis may provide insight into an image's pixel value distribution. Original images typically exhibit distinct patterns and biases in their histograms, reflecting features like dominant colors, shapes, and textures [33][34][35][36]. Secure encryption techniques aim to disrupt these patterns and create a more uniform distribution of pixel values in the encrypted image's histogram.…”
Section: Analytical Histogrammentioning
confidence: 99%
“…One distinctive feature of the proposed model is its integration of deep learning techniques for glaucoma detection with ensemble semantic segmentation for the optic disc and optic cup. While previous studies have looked at deep learning models for structure segmentation alone [29], the suggested approach introduces a novel ensemble framework that combines the predictions of multiple models. The accuracy and robustness of the glaucoma detection system can be enhanced by learning from a bigger pool of information through the combination of different models.…”
Section: The Modelmentioning
confidence: 99%
“…The ability to recognize and categories sick areas in plant images make image segmentation a valuable tool for studying plant diseases. A well-liked unsupervised machine learning approach called K-means clustering separates a picture into groups or segments depending on how similar the pixel intensity values are [2]. However, there is a possible production failure due to various diseases because of the high area under tomato cultivation and low efficiency (20 tonnes per hectare).…”
mentioning
confidence: 99%